English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-02-13 15:36:34 · 6 answers · asked by alona p 1 in Science & Mathematics Mathematics

6 answers

4xy^2

2007-02-13 15:41:56 · answer #1 · answered by Runa 7 · 0 0

√(16x^2y^4)=√16 * √x^2 * √y^4=+/-4*x*y^2=+/-4xy^2

2007-02-14 00:06:18 · answer #2 · answered by yupchagee 7 · 0 0

The answer should be 4xy^2.

2007-02-13 23:41:24 · answer #3 · answered by Juni Mccoy 3 · 1 0

sqrt(16*x^2*y^4) = sqrt(16) * sqrt(x^2) * sqrt(y^4) = sqrt(4^2) * sqrt(x^2) * sqrt((y^2)^2) = 4 * x *y^2

Note: sqrt(a^2) = a, since sqrt(a^2) = (a^2) ^(1/2) = a^(2 * (1/2)) = a

2007-02-13 23:42:44 · answer #4 · answered by I c y 1 · 0 0

there is no work.. just square root every part of the expression since its a monomial..

4xy^2

2007-02-13 23:39:23 · answer #5 · answered by teekshi33 4 · 1 0

4xy^2

2007-02-13 23:46:37 · answer #6 · answered by Helper X 2 · 0 0

fedest.com, questions and answers